Nudging credit scores in the field: The effect of text reminders on creditworthiness in the United States - Anat Bracha; Stephan Meier (Federal Reserve Bank of Boston, 2015)
In this paper we present evidence from a field experiment on the effect of text message reminders and credit card APR (annual payment rate) information on credit scores of low-to-moderate-income individuals. We find that individuals who initially had a low credit score benefited significantly from receiving the text reminders, while individuals who initially had a mid or high score did not. The positive effect on low-score individuals stems from the reduction of debt and better payment patterns. For mid-score individuals, we find a positive effect on payment patterns but no effect on credit scores; this may be because a better payment pattern is slower than a worse payment pattern to affect a credit score. For initially high-credit score individuals, we find a negative effect on credit scores, due to higher collection accounts. As for APR information, we find only sporadic effects: it helped reduce the number of inquiries for low-score individuals and reduce collection accounts of mid-score individuals, yet it contributed to greater past-due balances of high-score individuals.
Keywords: C93; D14; 330; field experiment; credit score; creditworthiness; reminders; financial decisionmaking; low income